Differential Cortical c-Fos and Zif-268 Expression after Object and Spatial Memory Processing in a Standard or Episodic-Like Object Recognition Task - Barbosa, Flávio F.; Santos, José Ronaldo; Meurer, Ywlliane S.; Macêdo, Priscila T.; Ferreira, Luane M.; Pontes, Isabella M.; Ribeiro, Alessandra M.; Silva, Regina H. (Frontiers in Behavioral Neuroscience, 2013)
Episodic memory reflects the capacity to recollect what, where and when a specific event happened in an integrative manner. Animal studies have suggested that the medial temporal lobe and the medial pre-frontal cortex are important for episodic-like memory formation. The goal of present study was to evaluate whether there are different patterns of expression of the immediate early genes c-Fos and Zif-268 in these cortical areas after rats are exposed to object recognition tasks with different cognitive demands. Male rats were randomly assigned to five groups: home cage control (CTR-HC), empty open field (CTR-OF), open field with one object (CTR-OF + Obj), novel object recognition task (OR) and episodic-like memory task (ELM) and were killed one hour after the last behavioral procedure. Rats were able to discriminate the objects in the OR task. In the ELM task, rats showed spatial (but not temporal) discrimination of the objects. We found an increase in the c-Fos expression in the dorsal dentate gyrus (DG) and in the perirhinal cortex (PRh) in the OR and ELM groups. The OR group also presented an increase of c-Fos expression in the medial prefrontal cortex (mPFC). Additionally, the OR and ELM groups had increased expression of Zif-268 in the mPFC. Moreover, Zif-268 was increased in the dorsal CA1 and perirhinal cortex only in the ELM group. In conclusion, the pattern of activation was different in tasks with different cognitive demands. Accordingly, correlation tests suggest the engagement of different neural networks in the object recognition tasks used. Specifically, perirhinal-dentate gyrus co-activation was detected after the what-where memory retrieval, but not after the novel object recognition task. Both regions correlated with the respective behavioral outcome. These findings can be helpful in the understanding of the neural networks underlying memory tasks with different cognitive demands.